2020
DOI: 10.1098/rsbl.2020.0792
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional dental topography and feeding ecology in the extinct cave bear

Abstract: The cave bear ( Ursus spelaeus s.l .) was an iconic extinct bear that inhabited the Pleistocene of Eurasia. The cause of extinction of this species is unclear and to identify the actual factors, it is crucial to understand its feeding preferences. Here, we quantified the shape descriptor metrics in three-dimensional (3D) models of the upper teeth (P 4 –M 2 ) of the cave bear to make inferences about its controversial feeding behaviour. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…General patterns in diet-based variation in DNE among mammals typically suggest a negative correlation between DNE and frugivory, and an increase in DNE in omnivorous and insectivorous taxa (Berthaume et al, 2019a; Fulwood et al,2021; Winchester et al, 2014). Our finding that values of DNE are instead broadly similar in frugivorous, insectivorous and omnivorous noctilionoid bats confirms previous findings from a smaller sample of species (López-Aguirre et al, 2021b), indicating a clear deviation from the general mammalian pattern in these bats (Fulwood et al, 2021; Pérez-Ramos et al, 2020; Winchester et al, 2014). This suggests a unique pattern of morphological adaptation to frugivory in noctilionoid bats, at least in the dentition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…General patterns in diet-based variation in DNE among mammals typically suggest a negative correlation between DNE and frugivory, and an increase in DNE in omnivorous and insectivorous taxa (Berthaume et al, 2019a; Fulwood et al,2021; Winchester et al, 2014). Our finding that values of DNE are instead broadly similar in frugivorous, insectivorous and omnivorous noctilionoid bats confirms previous findings from a smaller sample of species (López-Aguirre et al, 2021b), indicating a clear deviation from the general mammalian pattern in these bats (Fulwood et al, 2021; Pérez-Ramos et al, 2020; Winchester et al, 2014). This suggests a unique pattern of morphological adaptation to frugivory in noctilionoid bats, at least in the dentition.…”
Section: Discussionsupporting
confidence: 90%
“…Higher dental complexity has been proposed as a common adaptation for frugivory in bats (López-Aguirre et al, 2021b; Santana et al, 2011), contrary to recent studies that have found an opposite pattern in ursid carnivorans and strepsirrhine primates (Fulwood et al, 2021; Pérez-Ramos et al, 2020). Our results support the general chiropteran pattern of higher dental complexity in frugivores, as indicated by our results of OPCR in noctilionoid bats.…”
Section: Discussionmentioning
confidence: 84%
“…From a biomolecular perspective, traditional isotopic methods based on δ 15 N and δ 13 C from bulk protein (collagen), and more recently δ 15 N analyses of individual amino acids, were used to reconstruct the cave bear's dietary preferences. These studies essentially support a herbivorous diet across its range [41][42][43][44][45]. Palaeogenomic studies have revealed a complex evolutionary history within the cave bear species complex with three major groups: the Caucasian group including praekudarensis and kudarensis taxa; the European group including spelaeus, ingressus, eremus, and kanivetz from the Ural Mountains; and the Ural-specific group made up by rossicus [40].…”
Section: Cave Bearsmentioning
confidence: 81%
“…Likewise, the borophagine canid Tomarctus and paleomustelid Promartes lepidus are morphologically comparable to crown group representatives of their respective families and so may be expected to exhibit similar dietary profiles. In contrast, the cave bear Ursus spelaeus is closely related to the living brown and polar bears but, on the basis of its craniodental morphology and tooth wear patterns, has been inferred to be a tough plant specialist, generalized omnivore, or seasonal bone cracker (Jones and DeSantis, 2016; Peigné et al, 2009; Pérez-Ramos et al, 2020; Pinto-Llona, 2013; van Heteren et al, 2014), while the daphoenine amphicyonid Daphoenus and the stem carnivoran ”Miacis” latidens have no close extant relatives. Including these taxa in our sample presents an opportunity to gain novel insights into their paleoecology.…”
Section: Methodsmentioning
confidence: 99%